2020
DOI: 10.1136/vetreccr-2019-001026
|View full text |Cite
|
Sign up to set email alerts
|

Renal nephroblastoma in a 10‐month‐old boxer

Abstract: A 10-month-old male entire Boxer dog was presented for weight loss and abdominal distension with a large mass palpable within the abdomen. A unilateral nephrectomy was performed for a large renal nephroblastoma (30-cm diameter). The nephroblastoma was suspected stage I, with favourable histology (human Wilms tumour grading). No adjunctive chemotherapy was administered. The dog remains clinically well 27 months postnephrectomy. Renal nephroblastomas are rare canine neoplasms and reported survival time is variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…A literature review identified 21 case reports and one retrospective study evaluating five reported cases (Table 2). [1][2][3][4][5]7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In the literature, variable tumour biological features have been reported. Historically, survival times have been very poor, with the survival time ranging 0-6 months in the 2006 retrospective study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A literature review identified 21 case reports and one retrospective study evaluating five reported cases (Table 2). [1][2][3][4][5]7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In the literature, variable tumour biological features have been reported. Historically, survival times have been very poor, with the survival time ranging 0-6 months in the 2006 retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive chemotherapy after surgery is generally considered beneficial in patients with nephroblastoma. 3,5,6,8,24 In people, renal nephroblastoma is treated by nephrectomy, unless it has bilateral involvement or evidence of metastasis. 9 Utilising chemotherapy, with or without radiation therapy as adjunctive therapy, depends on the tumour stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations